Measuring the short-term success of hill dipterocarp forest restoration: the use of organic materials - Heriansyah, Ika; Abdul Hamid, Hazandy; Nuruddin, Ahmad Ainuddin; Abdu, Arifin; Ibrahim, Shamsudin (Canadian Center of Science and Education, 2013)
Restoring degraded logged-over forest which is indicated by low in soil fertility and organic matter due to imbalance nutrient cycle are of paramount importance as there has been increasing attention towards these forests as the sustainable use of these resources. Forest restoration through reintroduces tree species lost, especially fast growing dipterocarp is implemented to curtail degraded logged-over forest and improve the soil fertility through organic material application is important, but only few information is available on restoration of degraded forest. The objectives of this study were: (1) to evaluate the growth and biomass accumulation on different kind and application rate of organic materials; and (2) to determine suitable application for restoration of degraded forest in the humid tropics of Peninsular Malaysia. This study was conducted at Shorea leprosula stand in Tekai Forest Reserve, Pahang, Malaysia. To evaluate the effects of organic materials on survival, growth and biomass increment, mineral soils were amended with different application rates of organic materials, such as pulp mill sludge, compost, oil palm mesocarp and their combinations. Application rate of each organic materials were 0, ?, ½, ?, and ¾ of v/v. Growth measurement was conducted in every month for early growth up to 3 months after application and continued for every three months, while biomass accumulation were measured on initial, 3-, 6- and 12-month after application by destructive sampling method. Plant growth and biomass accumulation was increased by all amendments, however their rates was decreased during early growth as a result of adaptation process. Up to 12 months analyses, the best diameter growth performance appeared by compost 66.67% (treatment 9) and combination 33.33% (treatment 17), followed by treatment 10 (compost 75%) and 18 (combination 50%), while the best height growth performance appeared by treatment 18 and 17 and followed by treatment 9. The biggest biomass increment was on treatment 9, followed by treatment 18 and 17. The treatment that should be avoided for restoration program were control (treatment 1; only mineral soil), all application rates of pulp mill sludge and mix organic materials which high rate of sludge. Root formations on sludge medium shown in broken-down condition since they absorb water and dissolved minerals from pulp mill sludge medium, moreover all leaves shown unhealthy and burned down. Restoration program in tropical degraded forest land without applied organic material indicated poor growth rate and biomass accumulation, then organic material application to be one of the requirement treatments needed for better results. Compost as well as the type of past forest structure were important factors which resulted the best growth performance with high survival rate and recommended for restoration technique in Tekai Forest Reserve, Pahang, Malaysia or other comparative areas.